2022
DOI: 10.1073/pnas.2209975119
|View full text |Cite
|
Sign up to set email alerts
|

Driving force and pathway in polyelectrolyte complex coacervation

Abstract: There is notable discrepancy between experiments and coarse-grained model studies regarding the thermodynamic driving force in polyelectrolyte complex coacervation: experiments find the free energy change to be dominated by entropy, while simulations using coarse-grained models with implicit solvent usually report a large, even dominant energetic contribution in systems with weak to intermediate electrostatic strength. Here, using coarse-grained, implicit-solvent molecular dynamics simulation combined with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 129 publications
(192 reference statements)
5
69
0
Order By: Relevance
“…Generally speaking, they are unequal, which can be demonstrated using a more refined analysis. The result similar to eq has been recently reported for the spinodal concentration in the case of conventional PE–PE complex coacervation, which is also preceded by the formation of finite-size neutral pairs (globules). …”
Section: Inhomogeneous Internal Structure Of Strongly Adsorbed Layerssupporting
confidence: 88%
See 2 more Smart Citations
“…Generally speaking, they are unequal, which can be demonstrated using a more refined analysis. The result similar to eq has been recently reported for the spinodal concentration in the case of conventional PE–PE complex coacervation, which is also preceded by the formation of finite-size neutral pairs (globules). …”
Section: Inhomogeneous Internal Structure Of Strongly Adsorbed Layerssupporting
confidence: 88%
“…Generally speaking, they are unequal, which can be demonstrated using a more refined analysis. The result similar to eq has been recently reported for the spinodal concentration in the case of conventional PE–PE complex coacervation, which is also preceded by the formation of finite-size neutral pairs (globules). Similar reasoning applied to regimes II and III yields B n p I I R 3 ( 1 ξ e R e R / ξ e ) prefix− ξ e R 2 normale R / ξ e B n p I I I R 3 ( 1 H I I I R e false( Q / q q false) 4 / 3 false( ξ e / R false) 5 / 3 ) prefix− H I I I R 2…”
Section: Inhomogeneous Internal Structure Of Strongly Adsorbed Layerssupporting
confidence: 84%
See 1 more Smart Citation
“…62,63 Complex coacervation was also studied theoretically. 64,65 The first model that was able to phenomenologically capture the phase behavior of complex coacervates is the Voorn-Overbeek theory. 66,67 Essentially, the Voorn-Overbeek theory describes the mixing free energy of the system as a combination of the translational entropy within the Flory-Huggins theory framework, and the electrostatic attraction using the Debye-Hu ¨ckel theory.…”
Section: Stoichiometric Polyelectrolyte Complexesmentioning
confidence: 99%
“…For example, Muthukumar has recently discussed this type of charge-based mode-coupling effect in polyelectrolyte solutions where additional relaxation modes were predicted and observed experimentally. , It is currently not clear whether these charge fluctuation effects are generally suppressed by neutralization accompanying polymer complexation in our case, which gives added interest for the present observations. The formation of soluble ion pairs via interpolyelectrolyte neutralization in dilute solution was observed by isothermal titration calorimetry and in the dilute phase after phase separation with vanishingly small free polyelectrolytes by simulation . Moreover, additional relaxation processes are conceivable from the presence of ion–dipole, dipole–dipole, and multipole interactions that can arise when oppositely charged chain segments form complexes. , The DLS study by Kostko et al found that the viscoelasticity of high molecular mass polymer solutions led to observed deviations from the KF theory in near-critical solutions of this kind.…”
mentioning
confidence: 99%